2015
DOI: 10.1007/s11442-015-1184-9
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance impacts of land use change on biodiversity conservation priority areas across China: 1990–2010

Abstract: Land use change is one of the main drivers of biodiversity loss. In the last 20 years, China's land use pattern has undergone profound changes. This study constructs an Ecosystem Comprehensive Anthropogenic Disturbance Index (ECADI) to assess disturbance impacts of land use change between 1990 and 2010 on biodiversity conservation priority areas at national and regional scales. Four levels of biodiversity conservation areas were categorized: generally important areas, moderately important areas, important area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…This pressure affects land-use dynamics [10]. It is a significant risk factor for habitat quality [11,12], specifically through the expansion of agriculture, which triggers fragmentation of land [13] by aggravating the destruction of natural The area has diverse topographic features, including flat land, hills, plains, gorges, and steep slopes. Several permanent rivers and a temporal stream flowing into the Omo-Gibe River.…”
Section: Introductionmentioning
confidence: 99%
“…This pressure affects land-use dynamics [10]. It is a significant risk factor for habitat quality [11,12], specifically through the expansion of agriculture, which triggers fragmentation of land [13] by aggravating the destruction of natural The area has diverse topographic features, including flat land, hills, plains, gorges, and steep slopes. Several permanent rivers and a temporal stream flowing into the Omo-Gibe River.…”
Section: Introductionmentioning
confidence: 99%
“…HD is defined as an index to quantify the degree of resource utilization, environmental development, and reformation of nature in a certain region, which are reflected by LCC. It can be calculated as follows: where S CLE is area of equivalent construction area; S is areas totally; SL i is area of landuse type i, i=1, 2,..., n; CI i is a conversion factor (Table 1), which was used to compare the different degrees of human activities on the land surface, and its value was defined by referring to Zhao et al, Xu et al and Zhu et al [25][26][27]. Table 1.…”
Section: Quantitative Methods Of Human Activitiesmentioning
confidence: 99%
“…According to the spatial autocorrelation analysis, in terms of spatial autocorrelation types, these four hotspots are high-low aggregation type. Zhao et al [48] reported that cropland expansion was widespread in Sanjiang Plain from 1990-2010, which largely led to habitat fragmentation of the endangered species in this region. Isolated wetland has become an important habitat for threatened species in the northern part of Sanjiang Plain.…”
Section: Threatened Plant Biodiversity Conservation: Problems and Recmentioning
confidence: 99%
“…Land cover changes may also affect the distribution of threatened species [15]. Land use and land cover have changed rapidly over recent decades in Northeast China [48], especially species associated with cropland habitats. With the fragmentation and loss of natural wetlands attributed to cropland development, the habitat structures of threatened species may change.…”
Section: Uncertainty Of the Present Studymentioning
confidence: 99%